Numerical study of the induction of intratumoral apoptosis under microwave ablation by changing slot length of microwave coaxial antenna - Kim, Hyunjung; Kim, Donghyuk (Medical and Biological Engineering and Computing, 2024)
Recent advances in technology have led to an increase in the detection of previously undetected deep-located tumor tissue. As a result, the medical field is using a variety of methods to treat deep-located tumors, and minimally invasive treatment techniques are being explored. In this study, therapeutic effect of microwave ablation (MWA) on tumor generated inside liver tissue was analyzed through numerical analysis. The distribution of electromagnetic fields in biological tissues emitted by microwave coaxial antenna (MCA) was calculated through the wave equation, and the thermal behavior of the tissue was analyzed through the Pennes bioheat equation. Among various treatment conditions constituting MWA, tumor radius and the slot length inside the MCA were changed, and the resulting treatment effect was quantitatively confirmed through three apoptotic variables. As a result, each tumor radius has optimal power condition for MWA, 2.6W, 2.4W, and 3.0W respectively. This study confirmed optimal therapeutic conditions for MWA. Three apoptotic variables were used to quantitatively identify apoptotic temperature maintenance inside tumor tissue and thermal damage to surrounding normal tissue. The findings of this study are expected to serve as a standard for treatment based on actual MWA treatment. Graphical abstract: (Figure presented.)
Keywords: Apoptotic; Coaxial antennas; Medical fields; Microwave ablation; Microwave coaxial antenna; Minimally invasive treatments; Slot length; Thermal damage; Treatment techniques; Tumour tissue; Apoptosis; Microwave ablation; Microwave coaxial antenna; Slot length; Thermal damage